2013
DOI: 10.18585/inabj.v5i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Adiposopathy and Obesity Paradox

Abstract: BACKGROUND: Obesity has reached global epidemic proportions in both adults and children and is associated with numerous comorbidities, including hypertension, type 2 diabetes mellitus (T2DM), dyslipidemia and major cardiovascular diseases (CVD).CONTENT: Adiposity may cause adipocyte and adipose tissue anatomic and functional abnormalities, termed adiposopathy (adipose-opathy) or "sick fat," that result in endocrine and immune derangements. Adiposopathy may directly contribute to CVD through pericardiac and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Adiposopathy causes pericardiac and perivascular effects on the heart muscle and blood vessels which directly impact cardiovascular disease. Besides, adiposopathy also causes increased risk factors for diabetes mellitus, hypertension, and dyslipidemia (23). Previous studies found a significant relationship between central obesity through measurement of waist and hip ratios and the incidence of hypertension (p=0.007) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Adiposopathy causes pericardiac and perivascular effects on the heart muscle and blood vessels which directly impact cardiovascular disease. Besides, adiposopathy also causes increased risk factors for diabetes mellitus, hypertension, and dyslipidemia (23). Previous studies found a significant relationship between central obesity through measurement of waist and hip ratios and the incidence of hypertension (p=0.007) (20).…”
Section: Discussionmentioning
confidence: 99%